2016
DOI: 10.1007/s10006-016-0553-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumour of the maxilla

Abstract: Inflammatory pseudotumour (IP), also known as inflammatory myofibroblastic tumour (IMT), is a rare lesion of the maxillofacial skeleton and a diagnosis by exclusion. We describe three cases which affected the maxilla, two women and one man of ages 67, 56 and 70 years at presentation. All showed the typical, rather non-specific histopathological features. IgG4-positive plasma cells varied greatly in prominence, and none of the three lesions expressed ALK-1. Both women responded to steroids and radiotherapy, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…1 In this regard, Kichenaradjou et al recommend longer follow-up periods due to the unpredictable behavior of these tumors. 12 However, the follow-up period we employed is in line with that published by the majority of the authors: Tay and Balakrishnan (12 months), 2 Yan and Hu (12 months), 6 Suzuki et al (14 months), 7 Do et al (6 months), 9 Kieu et al (12 months), 10 Girardi et al (14 months). 13 We have considerably reduced the comorbidity and suffering of these patients by applying these measures.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…1 In this regard, Kichenaradjou et al recommend longer follow-up periods due to the unpredictable behavior of these tumors. 12 However, the follow-up period we employed is in line with that published by the majority of the authors: Tay and Balakrishnan (12 months), 2 Yan and Hu (12 months), 6 Suzuki et al (14 months), 7 Do et al (6 months), 9 Kieu et al (12 months), 10 Girardi et al (14 months). 13 We have considerably reduced the comorbidity and suffering of these patients by applying these measures.…”
Section: Discussionsupporting
confidence: 58%
“…Due to the high recurrence and morbidity rates associated with surgery and the good response to corticosteroids, some authors prefer to use corticosteroids as initial therapy. 1,3, [10][11][12][13][14] In our case, we used methylprednisolone as first-line treatment instead of surgery. The lesion is in complete remission.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report by Neronov et al, 25 cases of intraosseous IPT of the jaw were reported, with the mandible being the most affected. After an extensive literature search, less than 10 cases of maxillary IPT were found, 3 , 11 , 12 all of which were osteolytic. Two cases were on the right side, and seven were on the left.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy can be employed as therapeutic modality instead of oral corticosteroid therapy and has been known to produce tumor free survival [11].…”
Section: Discussionmentioning
confidence: 99%